Spatial dynamics of weeds in irrigated corn - O'Meara, Scott, author; Westra, Phil, advisor; Khosla, Rajiv, advisor; Brown, Cynthia, committee member; Reich, Robin, committee member (Colorado State University. Libraries, 2011)
To view the abstract, please see the full text of the document.
Keywords: control; dynamics; precision; spatial; weed